2022
DOI: 10.54488/ijcar.2022.307
|View full text |Cite
|
Sign up to set email alerts
|

Une intervention de groupe brève pour favoriser le bien-être des femmes enceintes pendant la pandémie de COVID-19 et soutenir la résilience des familles

Abstract: Contexte : La pandémie de COVID-19 a été associée à une augmentation de la détresse psychologique chez les femmes enceintes. Le présent article vise à évaluer l’acceptabilité du programme STEP-COVID (Soutenir la Transition et l’Engagement dans la Parentalité dans le contexte de la pandémie de COVID-19), une intervention prénatale de groupe en ligne, en mode synchrone, visant à soutenir le bien-être, la mentalisation et la résilience. Méthode : Vingt et une femmes enceintes québécoises ont participé au pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Second, as shown in a previous study (Berthelot et al., 2022), some participants identified that the program led to new insights about their functioning and the impact of their traumatic past. They reported sharing their insights with their partners, which contributed to a shared benevolent understanding of themselves.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Second, as shown in a previous study (Berthelot et al., 2022), some participants identified that the program led to new insights about their functioning and the impact of their traumatic past. They reported sharing their insights with their partners, which contributed to a shared benevolent understanding of themselves.…”
Section: Discussionmentioning
confidence: 63%
“…A preliminary evaluation of STEP‐COVID showed that women who participated in the intervention, and not women receiving treatment‐as‐usual (TAU), showed a significant decrease in psychological distress and a significant increase in positive affectivity over the course of pregnancy (Berthelot et al., 2023). Participants in STEP‐COVID also reported significant changes during the program on resilience‐promoting factors (Berthelot, Drouin‐Maziade, et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings that a brief online intervention could contribute to mitigating psychological distress and post-traumatic symptoms, increasing positive affectivity, enhancing resilience, improving the quality of the relationship with the partner and supporting a more positive view of self in pregnant women during the COVID-19 pandemic has important implications for clinical practice and public health. The results also offer additional support concerning the acceptability of STEP programs 48,49 and the effectiveness of mentalization-based interventions during the prenatal period 22,[50][51][52] .…”
Section: Discussionmentioning
confidence: 67%